Model Sosialisasi Pemilihan Presiden 2019 di Komisi Independen Pemilihan Kota Banda Aceh - Siti Hardiyanti; Muryanto Amin; Warjio Warjio (Universitas Medan Area, 2021)
This research explains how the socialization model carried out by the Banda Aceh KIP in the 2019 Election is an effort to provide an understanding of the election to the public. the implementation of the socialization model in collaboration with various communities / organizations is greatly enhanced. The theory used is the socialization theory, S.N. Eisentadl, with the concepts used in information communication based on two models: the participatory socialization model and the repressive socialization model. This study used a qualitative method with interviews as the main technique of data collection, then the data that had been obtained were analyzed in terms of content. The results of the research on the socialization model carried out by KIP are in the form of cooperation (socialization cooperation) with various organizations / communities, which include: KIP LSM Radar, KIP GPS, KIP to BEM Unsyiah, Socialization to the family base, socialization to KPI. Information communication is carried out by KIP in the context of cooperation with working partners. When the socialization is carried out on the initiative of the organization and is present at the place of socialization voluntarily, the socialization is categorized as a participatory socialization model. Whereas the concept of information communication is tiered from political values and political feelings studied from the material presented by KIP which includes political education material, such as: citizens' rights and obligations, voting procedures, introduction of ballot papers, checking DPT, and procedures for administering Forms. A5. The implication is that the people of Banda Aceh already understand and have a pattern of awareness of the socialization material delivered by KIP